COMPLICATIONS OF TERMINAL COLOSTOMY IN PATIENTS WITH TUMOROUS LARGE INTESTINE ILEUS AND THEIR SURGICAL MANAGEMENT - S. A. Aliev; B. M. Zeinalov; E. S. Aliev (Вестник хирургии имени И.И. Грекова)
The article analyzed the structure, incidence rate and results of surgical treatment of paracolostomal complications in 69 patients out of 134 (aged from 23 to 77 years old). The patients were divided into 2 groups according to the variant of terminal colostomy. The single-barrel colostomy was formed by classical (intraperitoneal) method using «proboscis» design in 58 patients (43,3%) of the first group. Various complications were developed in the area of colostomy in 42 (72,4%) patients. The single-barrel flat colostomy was applied at the skin level using the method modified by the authors in 76 (56,7%) patients of the second group. The authors designed the method of controlled intra- and postoperative decompression and lavage of the colon by a new model of aspiration-irrigation device in order to unload the colon through colostomy. There were noted complications in the area of colostomy in 27 (35,5%) cases. The developed rational method of terminal colostomy formation, upgrading the ways of intra- and postoperative decompression and lavage of the colon facilitated to decrease of the rate of postcolostomy complications more than two times (from 72,4 to 35,5%). The author’s method led to optimization of immediate and long-term results of surgical treatment.